Artists and the Arab Uprisings - Schwartz, Lowell H. (RAND Corporation, 2013)
Regional artists can play a positive role in shaping public debate and supporting democratic transition in the Middle East. This report explores the challenges artists have faced since the Arab uprisings, U.S. government programs to support arts in the region, and the wide array of nongovernmental activities to engage Arab artists, offering recommendations to improve support for these artists.